Sulfide removal from petroleum refinery wastewater using hydrogen peroxide and chemically modified activated carbon - Mariah, Che Mamat (2022)
Petroleum refinery plants generate wastewater, solid waste and sludge composed of organic, inorganic compounds including heavy metals. Further treatment is needed for petroleum refinery wastewater because it typically has high concentration of sulfide which is known as the most hazardous pollutants. It is released to environment as dissolved sulfide (S2- and HS-) in effluents and H2S in waste gases. Thus, it is very important to remove sulfide from petroleum refinery wastewater that can bring harmful to human and environmental problems because of their alkalinity and high sulfide level. The objective in this study is to determine the ability of hydrogen peroxide (H2O2) and chemically modified activated carbon (AC-M) as a new approach studies in sulfide removal from petroleum refinery wastewater. The effect caused by these hazardous pollutants and growing concern on environmental issues led to remove sulfide from petroleum refinery wastewater using oxidation method and adsorption method in this study. Result shows the best concentration of sulfide simulated wastewater is 300 mg/L, H2O2 dosage is 1.5 ml and reaction time is 30 min in oxidation process. While, the best concentration of sulfide simulated wastewater is 100 mg/L, AC-M dosage is 0.5 g and contact time is 6 hr in adsorption process. The prepared AC-M was characterized using SEM, EDX, BET, and FTIR. The kinetic studies of the adsorption behaviour of AC-M have shown that Freundlich adsorption isotherm is fitted well and the adsorption process followed Pseudo-second order kinetic model. The comparative between oxidation and adsorption method using the best parameters on sulfide removal from actual petroleum refinery wastewater was determined. The efficiency of oxidation method which is able to remove sulfide concentration is 99.83% from 300 mg/L to 0.5 mg/L, COD concentration is 98.29% from 4100 mg/L to 70 mg/L, and pH is 29.08% from 11.86 to 8.41. While, the efficiency of adsorption method which is able to remove sulfide concentration is 95.70% from 100 mg/L to 4.3 mg/L, COD concentration is 98.29% from 4100 mg/L to 70 mg/L, and pH is 3.0% from 12.00 to 11.65. Thus, it is concluded that oxidation method more effective than adsorption method in sulfide removal from spent caustic. However, both methods were able to remove more than 90% removal especially on sulfide and COD concentration. It is recommended that oxidation method hybrid with adsorption method to provide more efficiency of sulfide removal. The information obtained from this study is useful for scale up purpose in the petroleum refining industry.